BiOI nanoparticle/PCN-222 heterojunctions as self-decontaminating photocatalysts with efficient tetracycline visible-light degradation. Issue 43 (18th October 2022) - Zhang, Heyao; Meng, Qing; Li, Huijie; Wu, Gaigai; Li, Ke; Xu, Jinghan; Wang, Lianlian; Wu, Jie; Meng, Xiangru; Hou, Hongwei
Abstract : A series of BiOI@PCN-222- X (BP- X ) Z-scheme heterojunction photocatalysts were constructed, which showed well activity of tetracycline adsorption and photodegradation under visible light irradiation. Abstract : Herein, a series of crystalline Z-scheme photocatalytic heterojunctions BiOI@PCN-222 (BP- X, X donates Zr6 : Bi, X = 1, 3 and 5) are constructed by highly dispersed integration of BiOI into the channel of a porphyrin-based Zr-MOF PCN-222 through surface site engineering. BP- X exhibits stronger visible light absorption (400–800 nm) than that of PCN-222, while retaining the mesoporous nature with a surface area of ∼650 m 2 g −1 and large pore volume ∼15 Å in diameter. A set of characterization measurements reveal the formation of an internal interface electric field in the composite and the electron transfer from BiOI to PCN-222. In addition, their photocatalytic activity toward the degradation of tetracycline (TC) under visible light irradiation is investigated to illustrate the advantages of self-decontaminating photocatalysts capable of both adsorption and photodegradation. BP- X shows superior TC adsorption and photodegradation activity. Specially, the photodegradation kinetic rate constant k of BP-3 is 1.5 and 10 times higher than that of PCN-222 and BiOI, respectively. The improved photocatalytic performance of BP-3 is attributed to its strong TC adsorption capacity and highly dispersed Z-scheme heterojunction, which is beneficial to photogenerated charge separation and electron transfer. This work explored the opportunities to develop heterojunction mesoporous materials based on MOFs for self-purification and photodegradation of organic pollutants.